Lifetime prevalence of drugs use in adolescents - Gómez Bustamante, Edna; Cogollo Milanés, Zuleima (Investigación y Educación en Enfermería, 2012)
<!– [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–> Objective. To estimate the prevalence of lifetime use of psychoactive drugs in adolescents from Cartagena, Colombia. Methodology. Cross-sectional study carried out with a representative sample of 244 adolescents between 13 and 17 years of age from the general population. The study inquired on use of psychoactive drugs at any time of their lives (cocaine, ecstasy, inhalants, marihuana, or any drug that can be injected). The explanatory variables were adjusted through logistic regression. Results. Participants were from low and middle socio-economic levels. The lifetime prevalence of use of any drug was 20%. A total of 19% of the participants reported daily cigarette use and 18% had risky alcohol use. The following risk factors were related to drug use some time in their lives: daily cigarette use (OR=30.2; CI95%=11.8-77.6), not being religious (OR=5.8; CI95%=1.8- 18.8), male gender (OR=3.7; CI95%=1.1-13.1), and risky alcohol use (OR=3.5; CI95%=1.2-9.8). Conclusion. Use of any illegal drug some time in their lives by adolescents is high, constituting a healthcare problem, which should be addressed by government organizations. This use was related to male gender, not being religious, cigarette smoking, and having risky alcohol use.